2020
DOI: 10.3390/ma13122865
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Mechanical Properties and Porosity of Concrete Using Steel Slag Coarse Aggregate

Abstract: This paper investigates the possibility of utilizing steel slags produced in the steelmaking industry as an alternative to burnt clay brick aggregate (BA) in concrete. Within this context, physical, mechanical (i.e., compressive and splitting tensile strength), length change, and durability (porosity) tests were conducted on concrete made with nine different percentage replacements (0%, 10%, 20%, 30%, 40%, 50%, 60%, 80%, and 100% by volume of BA) of BA by induction of furnace steel slag aggregate (SSA). In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 29 publications
(46 reference statements)
3
19
0
Order By: Relevance
“…While there is research conducted into alternative methods of clinker production, for example, by Ellis et al [ 6 ], the most efficient and economically sound method of lowering the negative impact of clinker production is to use waste materials [ 7 ], make the more efficient use of cement in concrete and mortar production, and increase the substitution of clinker by supplementary cementitious materials [ 8 ]. The European Standardization Committee has begun to broaden the range of common cements in the working draft of standard prEN-197-5 [ 9 ] by extending the possibilities of using non-clinker main components in cements by introducing CEM II/C-M and CEM VI, which will include, respectively, up to 50 and 65% of supplementary cementitious materials.…”
Section: Introductionmentioning
confidence: 99%
“…While there is research conducted into alternative methods of clinker production, for example, by Ellis et al [ 6 ], the most efficient and economically sound method of lowering the negative impact of clinker production is to use waste materials [ 7 ], make the more efficient use of cement in concrete and mortar production, and increase the substitution of clinker by supplementary cementitious materials [ 8 ]. The European Standardization Committee has begun to broaden the range of common cements in the working draft of standard prEN-197-5 [ 9 ] by extending the possibilities of using non-clinker main components in cements by introducing CEM II/C-M and CEM VI, which will include, respectively, up to 50 and 65% of supplementary cementitious materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with 100% natural aggregate concrete, the requirements of numerous guidelines were met for classification as a good quality of concrete [ 21 ]. Similarly, it was found that 100% IFSSA is suitable as coarse aggregate to produce concrete without compromising the compressive and tensile strength [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fired clay brick aggregate (FCBA) is commonly used as coarse aggregate in most countries in South Asia, especially in Bangladesh [ 22 , 23 ]. Fired clay bricks are widely made by molding wet clay into the required shape and size and then burning these clay blocks in an open brickfield kiln at around 1000–1200 °C [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical and mechanical properties of concrete composites containing waste thermoplastic elastomer from the production process of car floor mats is presented by Ulewicz et al [ 12 ]. Miah et al [ 13 ] present the effect of steel slag aggregate as a substitute for conventionally used brick aggregate on the physical, mechanical and durability performances of concretes. In turn, Dobiszewska and Beycioğlu [ 14 ] show that waste basalt powder, which is a by-product of the production of mineral–asphalt mixtures, used as a partial sand replacement, increases the compressive strength of concretes.…”
mentioning
confidence: 99%